The National Planning Policy Framework and Archaeology: A Discussion - Joe Flatman; Dominic Perring (Papers from the Institute of Archaeology, 2013)
For twenty years, ‘rescue’ archaeology and cultural resource management in England lived within the certain world of Planning Policy Guidance Note 16: Archaeology and Planning (the PPG) (DoE 1990). The PPG gave our profession clear locus and status within the business of development and planning. Those who wished to disturb archaeological remains in order to build were effectively obliged to pay for the excavation and publication of those remains they could not preserve in situ – provided that local planners were prepared to take on board the conservation agenda described for them in the PPG. The PPG provided a new language of investigative procedure, built around deskbased assessments, field evaluations, written schemes of investigation, and programmes of mitigation (usually a combination of excavation and avoidance). Whilst the PPG relied on a series of contestable assumptions it gave archaeologists unprecedented access to sites and funds. A full obituary of the PPG would be long on its flaws, but those in professional practice benefitted from expanded horizons of archaeological employment and research (see Aitchison 2010, 2012). The policies set out within the PPG secured almost all of the advances made during the ‘rescue’ era of British archaeology in the 1970s and 80s whilst reducing our reliance on state funding.
Keywords: National Planning Policy Framework; planning; development